Genetic characterization and genotype-phenotype associations in a large cohort of patients with hypertrophic cardiomyopathy : an ancillary study of the Portuguese registry of hypertrophic cardiomyopathy - Lopes, Luis (2019)
© 2018 Elsevier B.V. All rights reserved.